1479 \noindent |
1479 \noindent |
1480 \begin{proof} |
1480 \begin{proof} |
1481 We prove this by induction on $r$. The base cases for $\RZERO$, |
1481 We prove this by induction on $r$. The base cases for $\RZERO$, |
1482 $\RONE $ and $\RCHAR{c}$ are straightforward. |
1482 $\RONE $ and $\RCHAR{c}$ are straightforward. |
1483 In the sequence $r_1 \cdot r_2$ case, |
1483 In the sequence $r_1 \cdot r_2$ case, |
1484 the inductive hypotheses state $\exists N_1. \forall s. \; \llbracket \rderssimp{r}{s} \rrbracket \leq N_1$ and |
1484 the inductive hypotheses state |
1485 $\exists N_2. \forall s. \; \llbracket \rderssimp{r_2}{s} \rrbracket \leq N_2$. We can reason as follows |
1485 $\exists N_1. \forall s. \; \llbracket \rderssimp{r}{s} \rrbracket \leq N_1$ and |
|
1486 $\exists N_2. \forall s. \; \llbracket \rderssimp{r_2}{s} \rrbracket \leq N_2$. |
|
1487 |
|
1488 When the string $s$ is not empty, we can reason as follows |
1486 % |
1489 % |
1487 \begin{center} |
1490 \begin{center} |
1488 \begin{tabular}{lcll} |
1491 \begin{tabular}{lcll} |
1489 & & $ \llbracket \rderssimp{r_1\cdot r_2 }{s} \rrbracket_r $\\ |
1492 & & $ \llbracket \rderssimp{r_1\cdot r_2 }{s} \rrbracket_r $\\ |
1490 & $ = $ & $\llbracket \rsimp{(\sum(r_1 \backslash_{rsimp} s \cdot r_2 \; \; :: \; \; |
1493 & $ = $ & $\llbracket \rsimp{(\sum(r_1 \backslash_{rsimp} s \cdot r_2 \; \; :: \; \; |
1491 \map \; (r_2\backslash_{rsimp} \_)\; (\vsuf{s}{r})))} \rrbracket_r $ & (1) \\ |
1494 \map \; (r_2\backslash_{rsimp} \_)\; (\vsuf{s}{r})))} \rrbracket_r $ & (1) \\ |
1492 & $\leq$ & $\llbracket \rdistinct{(r_1 \backslash_{rsimp} s \cdot r_2 \; \; :: \; \; |
1495 & $\leq$ & $\llbracket \rdistinct{(r_1 \backslash_{rsimp} s \cdot r_2 \; \; :: \; \; |
1493 \map \; (r_2\backslash_{rsimp} \_)\; (\vsuf{s}{r}))}{\varnothing} \rrbracket_r + 1$ & (2) \\ |
1496 \map \; (r_2\backslash_{rsimp} \_)\; (\vsuf{s}{r}))}{\varnothing} \rrbracket_r + 1$ & (2) \\ |
1494 & $\leq$ & $2 + N_1 + \rsize{r_2} + (N_2 * (card\;(\sizeNregex \; N_2)))$ & (3)\\ |
1497 & $\leq$ & $2 + N_1 + \rsize{r_2} + (N_2 * (card\;(\sizeNregex \; N_2)))$ & (3)\\ |
1495 $\rsize{(r_1 \cdot r_2) \backslash_r s}$& $\leq$ & $max \; (2 + N_1 + \llbracket r_2 \rrbracket_r + N_2 * (card\; (\sizeNregex \; N_2))) \; \rsize{r_1\cdot r_2}$ & (4) |
|
1496 \end{tabular} |
1498 \end{tabular} |
1497 \end{center} |
1499 \end{center} |
1498 \noindent |
1500 \noindent |
1499 (1) is by the corollary \ref{seqEstimate1}. |
1501 (1) is by the corollary \ref{seqEstimate1}. |
1500 (2) is by \ref{altsSimpControl}. |
1502 (2) is by \ref{altsSimpControl}. |
1501 (3) is by \ref{finiteSizeNCorollary}. |
1503 (3) is by \ref{finiteSizeNCorollary}. |
1502 (4) is by splitting the case when $s = []$ and $s \neq []$. |
1504 |
1503 |
1505 |
1504 We reason similarly for $\STAR$.\medskip |
1506 Combining the cases when $s = []$ and $s \neq []$, we get (4): |
|
1507 \begin{center} |
|
1508 \begin{tabular}{lcll} |
|
1509 $\rsize{(r_1 \cdot r_2) \backslash_r s}$ & $\leq$ & |
|
1510 $max \; (2 + N_1 + |
|
1511 \llbracket r_2 \rrbracket_r + |
|
1512 N_2 * (card\; (\sizeNregex \; N_2))) \; \rsize{r_1\cdot r_2}$ & (4) |
|
1513 \end{tabular} |
|
1514 \end{center} |
|
1515 |
|
1516 We reason similarly for $\STAR$. |
|
1517 The inductive hypothesis is |
|
1518 $\exists N. \forall s. \; \llbracket \rderssimp{r}{s} \rrbracket \leq N$. |
|
1519 Let $\n_r = \llbracket r^* \rrbracket_r$. |
|
1520 When $s = c :: cs$ is not empty, |
|
1521 \begin{center} |
|
1522 \begin{tabular}{lcll} |
|
1523 & & $ \llbracket \rderssimp{r^* }{c::cs} \rrbracket_r $\\ |
|
1524 & $ = $ & $\llbracket \rsimp{(\sum (\map \; (\lambda s. (r \backslash_{rsimp} s) \cdot r^*) \; (\starupdates\; |
|
1525 cs \; r \; [[c]] )) )} \rrbracket_r $ & (5) \\ |
|
1526 & $\leq$ & $\llbracket |
|
1527 \rdistinct{ |
|
1528 (\map \; |
|
1529 (\lambda s. (r \backslash_{rsimp} s) \cdot r^*) \; |
|
1530 (\starupdates\; cs \; r \; [[c]] ) |
|
1531 )} |
|
1532 {\varnothing} \rrbracket_r + 1$ & (6) \\ |
|
1533 & $\leq$ & $1 + (\textit{card} (\sizeNregex \; (N + n_r))) |
|
1534 * (1 + (N + n_r)) $ & (7)\\ |
|
1535 \end{tabular} |
|
1536 \end{center} |
|
1537 \noindent |
|
1538 (5) is by the lemma \ref{starClosedForm}. |
|
1539 (6) is by \ref{altsSimpControl}. |
|
1540 (7) is by \ref{finiteSizeNCorollary}. |
|
1541 Combining with the case when $s = []$, one gets |
|
1542 \begin{center} |
|
1543 \begin{tabular}{lcll} |
|
1544 $\rsize{r^* \backslash_r s}$ & $\leq$ & $max \; n_r \; 1 + (\textit{card} (\sizeNregex \; (N + n_r))) |
|
1545 * (1 + (N + n_r)) $ & (8)\\ |
|
1546 \end{tabular} |
|
1547 \end{center} |
|
1548 \noindent |
|
1549 |
|
1550 The alternative case is slightly less involved. |
|
1551 The inductive hypothesis |
|
1552 is equivalent to $\exists N. \forall r \in (\map \; (\_ \backslash_r s) \; rs). \rsize{r} \leq N$. |
|
1553 In the case when $s = c::cs$, we have |
|
1554 \begin{center} |
|
1555 \begin{tabular}{lcll} |
|
1556 & & $ \llbracket \rderssimp{\sum rs }{c::cs} \rrbracket_r $\\ |
|
1557 & $ = $ & $\llbracket \rsimp{(\sum (\map \; (\_ \backslash_{rsimp} s) \; rs) )} \rrbracket_r $ & (9) \\ |
|
1558 & $\leq$ & $\llbracket (\sum (\map \; (\_ \backslash_{rsimp} s) \; rs) ) \rrbracket_r $ & (10) \\ |
|
1559 & $\leq$ & $1 + N * (length \; rs) $ & (11)\\ |
|
1560 \end{tabular} |
|
1561 \end{center} |
|
1562 \noindent |
|
1563 (9) is by \ref{altsClosedForm}, (10) by \ref{rsimpSize} and (11) by inductive hypothesis. |
|
1564 |
|
1565 Combining with the case when $s = []$, one gets |
|
1566 \begin{center} |
|
1567 \begin{tabular}{lcll} |
|
1568 $\rsize{\sum rs \backslash_r s}$ & $\leq$ & $max \; \rsize{\sum rs} \; 1+N*(length \; rs)$ |
|
1569 & (12)\\ |
|
1570 \end{tabular} |
|
1571 \end{center} |
|
1572 (4), (8), and (12) are all the inductive cases proven. |
1505 \end{proof} |
1573 \end{proof} |
1506 |
1574 |
1507 \noindent |
1575 \noindent |
1508 |
1576 |
1509 %----------------------------------- |
1577 %----------------------------------- |